Chronic Pain and Chronic Opioid Use After Intensive Care Discharge – Is It Time to Change Practice? - Stamenkovic, Dusica M.; Laycock, Helen; Karanikolas, Menelaos; Ladjevic, Nebojsa Gojko; Neskovic, Vojislava; Bantel, Carsten (Frontiers in Pharmacology, 2019)
Almost half of patients treated on ICU experience moderate to severe pain. Managing pain in the critically ill patient is challenging, as their pain is complex with multiple causes. Pharmacological treatment often focuses on opioids, and over a prolonged admission this can represent high cumulative doses which risk opioid dependence at discharge. Despite analgesia the incidence of chronic pain after treatment on ICU is high ranging from 33-73%. Measures need to be taken to prevent the transition from acute to chronic pain, whilst avoiding opioid overuse. This narrative review discusses preventive measures for the development of chronic pain in intensive care unit (ICU) patients. It considers a number of strategies that can be employed including non-opioid analgesics, regional analgesia and nonpharmacological methods. We reason that individualized pain management plans should become the cornerstone for critically ill patients to facilitate physical and psychological well being after discharge from critical care and hospital.